Studies on the life history and aquaculture of the Mullet, Liza haematocheila distributed in the ariake sound - Anuar, Hassan (Japan: Nagasaki University, 2010)
Cruoricola lates N. Gen., N. Sp. from the blood vessels of cultured sea bass (Lates calcarifer Bloch 1790) is described. It is a lanceolate sanguinicolid with a single column of submarginal, ventral spines; extensive vitellarium; and X-shaped intestine. The single, lobed testis extends laterally to the caeca. The cirrus lies dorsal to the spherical seminal vesicle. Auxiliary seminal vesicle present. The uterus is post-ovarian, partly situated between the lobes of the ovary; mid-portion is thick. Cruoricola lates N. Gen., N. Sp. is found in all sea bass over 15g weight in the type locality, Pulau Ketam.